Mesenchymal Stromal Cell Immunology for Efficient and Safe Treatment of Osteoarthritis - Najar, Mehdi; Martel-Pelletier, Johanne; Pelletier, Jean-Pierre; Fahmi, Hassan (Frontiers in Cell and Developmental Biology, 2020)
Cell therapy is a promising strategy for regenerative medicine that seeks to repair damaged or injured tissue. Mesenchymal Stromal Cells (MSCs) is a valuable cellular product for cell-based therapy. These cells can be readily isolated from multiple sources and expanded ex vivo for possible clinical applications. MSCs possess a unique immunological profile and regulatory machinery that underline their therapeutic effects. They have also the capacity to sense the changes within the tissue environment to display the adequate response. Indeed, there is a close interaction between MSCs and their tissue of engraftment. Accordingly, MSCs are demonstrating encouraging results for a variety of disease. However, their effectiveness needs to be improved to reach the desired therapeutic goal. In this review, we selected to discuss the importance of their immunological features including the type of transplantation and route of delivery as well as the immune and blood compatibility of MSCs. It is important to consider MSCs immune evasive rather than immune privileged. We also highlighted some of the actions / mechanisms that are displayed during tissue healing including the response of MSCs to injury signals, their interaction with the immune system and the impact of their lifespan. The research field of MSCs is inspiring and innovating but requires more knowledge about their immuno-biological properties. A better understanding of these features will be key for developing a safe and efficient medicinal product for clinical use.